Mechanical Properties and Failure Behavior of Composite Samples - Hongwei Zhang; Zhijun Wan; Yuan Zhang; Dong Wu (Advances in Materials Science and Engineering)
In underground coal mining systems, the occurrences of coal burst hazards and pillar failures relate not only to the condition of stress distribution but also the geometry of roof-coal-floor structures. To study the failure response of these structures, the rock-coal-rock (RCR) sample, in which a coal component is sandwiched between rocks, is always employed as the experimental subject. In this study, the effect of height ratio (a ratio represents the height percentage of coal component in an RCR sample) on the mechanical properties and deformation behavior of RCR samples was numerically investigated by using the distinct element model (DEM). The results reveal the following. (1) The uniaxial compression strength (UCS) of the RCR sample decreases with increasing height ratio as an inverse proportional function. (2) With increasing height ratio, the elastic modulus of the RCR sample decreases exponentially, while the postpeak modulus is strengthened in an inverse proportional manner. (3) Microcracking activity of the RCR sample is different from that of the pure sample during loading. Specifically, a reactive period always occurs after the quiet and active periods in the RCR sample. (4) The RCR sample fails in a progressive manner, in which cracking bands develop preferentially in coal and then extend to rocks. Expectably, the mechanical properties and failure behavior of RCR samples are height ratio dependent, which may contribute to predicting the hazard of coal bursts and estimating the failure of rock-coal-floor structures.